Pengaruh Umur Pemain Tenis Lapangan Terhadap Ranking Dunia Di Jumlah Point Pemain Tenis Lapangan Menggunakan Metode Regresi Linear Sederhana - Gustian, Ifan (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2024)
This study aims to analyze the relationship between the number of points scored and the age of tennis players using a simple linear regression method. Data were collected from active players, including the points they earned in matches and their ages. Simple linear regression analysis was employed to determine the extent of the linear relationship between these two variables. The results indicate a correlation between players’ age and the number of points they obtain. The regression coefficients and their statistical significance are examined to assess the strength and relevance of this relationship. Findings from this research offer deeper insights into the factors that may influence on-court performance, with a particular focus on age. The discussion covers the interpretation of results, implications for tennis coaching and management, and potential applications in training programs. Study limitations and recommendations for future research are also addressed. Ultimately, this research is expected to contribute to a better understanding of the determinants of tennis performance, especially regarding the role of age.